Performance-Based Wind Engineering: Background and State of the Art - Spence, Seymour M. J.; Arunachalam, Srinivasan (Frontiers in Built Environment, 2022)
This paper surveys the rapidly growing field of performance-based wind engineering (PBWE) of engineered systems, with focus on not only how PBWE has evolved since its early incarnations inspired by performance-based seismic engineering, but also the unique challenges of PBWE and the research that continues to emerge to tackle them. The limitations of traditional prescriptive wind design approaches are discussed with the aim of illustrating how such approaches are inadequate for providing acceptable building performance during extreme wind events, thus motivating why performance-based strategies for wind engineering are gaining traction and are poised to complement, if not replace, current approaches to wind design. In this respect, the current state of knowledge on the factors that affect building performance via extreme structural response, damage to the envelope system, and nonstructural components, is reviewed and challenges are identified. Lastly, the potential benefit of integrating optimization methods is identified while acknowledging the computational difficulty associated with such approaches.